Pau Licious Café / Muhammad Akmal Muhamad Hamzah ... [et al.] - Muhamad Hamzah, Muhammad Akmal; Mohd Ali, Muhammad Ariff Alimi; Rozhan, Rabiatul Adawiyah; Mohamad Nazam, Nur Izzahtul Husna (2021)
Bao, also known as Pau in Malaysia, has been around for a long time and is usually seen at R&R or Chinese eateries. Pau Licious Cafe taking advantage of the fact that Pau is not that easy to find especially, for Muslims who live in the city. That is why the owner chose to open this business. The name of the café is Pau Licious Café, which indicates that we sell scrumptious pau. Pau Licious Cafe took the opportunity to be the first café that sells Pau as their main dish while selling other food as well. The focus of Pau Licious Café is to serve the most delicious pau with fast serving to customers, which is where the slogan “Pau for People” comes from. The premise is located at Lab 6 & 7 of Persiaran Setia Alam, Eco Ardence 40170 Shah Alam, Malaysia. The chosen location can be considered as a strategic place because it is located near the community that lives at the Sub Urban City which they considered as a modern people that would try some new and unique things like our dessert. The goal of the company is to become established as the leading manufacturer of the foods industry in Malaysia. To achieve this goal, Pau Licious Café's critical success factors will be to identify emerging trends and integrate them into our company operations, respond quickly to season changes, provide high-quality services, invest time and money in marketing and advertising, expand into specialty markets, and stay ahead of the "technology curve".